Redefinisi Pelayanan Kesehatan: Penerapan TOGAF ADM dalam Perencanaan Arsitektur Enterprise Puskesmas Mandiri - Fajrina, Berliana (Universitas Komputer Indonesia, 2024)
This journal has a problem on the data processing section, especially the patient registration service for treatment, which takes a long time in the Independent Puskesmas. Treatment and patient care processes are delayed due to the absence of an integrated system. At present, Puskesmas MANDIRI does not have an information system that can assist health processes and activities. Therefore, complex system planning of various aspects should be done using the Enterprise Architecture and TOGAF ADM approaches. This approach should be used to design business architectures, information architecture, data architecture and system-supporting application architecture. The stages of TOGAF ADM can be used to design an enterprise architecture, ranging from the preliminary phase to migration planning. The results of research show that planning an enterprising architecture using TOGF ADM may help Puskesmas Self improve the quality of service by developing an integrated information system, which can help vision and organization of the mission as well as facilitate business processes.